Benthic deep-sea fungi in submarine canyons of the Mediterranean Sea. (November 2018) - Barone, Giulio; Rastelli, Eugenio; Corinaldesi, Cinzia; Tangherlini, Michael; Danovaro, Roberto; Dell'Anno, Antonio
Highlights: Submarine canyons host abundant and diverse fungal communities. Fungal abundance, biomass and diversity are driven by carbohydrate concentrations. Deep-sea sediments can harbour a high number of novel fungal taxa. Thermohaline and trophic conditions may promote a high turnover diversity of fungi. Abstract: Fungi are ubiquitous components of microbial assemblages in aquatic ecosystems, but their quantitative relevance, ecological role and diversity in benthic deep-sea ecosystems are still largely unknown. Here, we investigated patterns and drivers of benthic fungal abundance, biomass and diversity from 200 to 1000 m depth in three submarine canyons of the Mediterranean Sea (Tricase, Crotone and Squillace canyons). The Crotone and Squillace canyons, which are close to the coast and influenced by river inputs, showed significantly higher fungal abundance, biomass and diversity (as operational taxonomic units, OTUs) compared with the Tricase canyon that was far from the coast and without nearby estuaries. Fungal biomass, abundance and diversity increased with increasing concentrations of carbohydrates, which in deep-sea sediments include highly refractory organic compounds. Overall, a total of 1742 fungal OTUs, belonging to all fungal phyla known to date, were found and Ascomycota represented the dominant phylum. However, only 36% of the reads belonged to known genera. In particular, Tricase and Crotone canyons hosted the highest proportion of unknown fungal taxa, suggesting that deep-sea sediments can harbour a high number of novel fungal lineages. Our findings also reveal that fungal assemblage composition in the investigated canyons was influenced by trophic and thermohaline conditions, which may promote a high turnover diversity of benthic deep-sea fungal assemblages. Overall results reported here indicate that the submarine canyons of the Mediterranean Sea can represent hot-spots of abundant and highly diversified fungal assemblages and pave the way for a better understanding of the ecological role of fungi in the largest ecosystem on Earth.